2009
DOI: 10.1128/jvi.01526-09
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation of the Nuclear Form of Varicella-Zoster Virus Immediate-Early Protein 63 by Casein Kinase II at Serine 186

Abstract: Varicella-zoster virus (VZV) open reading frame (ORF) 63 is abundantly transcribed in latently infectedhuman ganglia and encodes a 278-amino-acid protein, IE63, with immediate-early kinetics. IE63 is expressed in the cytoplasm of neurons during VZV latency and in both the cytoplasm and the nucleus during productive infection; however, the mechanism(s) involved in IE63 nuclear import and retention has remained unclear. We constructed and identified a recombinant monoclonal antibody to detect a posttranslational… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
9
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 37 publications
1
9
0
Order By: Relevance
“…Our identification of phosphorylation at Ser224 supports results that demonstrated that Ser224 was a target for CDK1 and that a Ser224Ala mutation altered localization of ORF63p and its transcriptional regulatory properties . Recently, we demonstrated that Ser186 was phosphorylated by CKII (Mueller et al, 2009), which is consistent with this study. Also, our identification of possible phosphorylation at Thr171 and/ or Ser173 (and to a lesser extent Ser12) confirms the work of Baiker et al (2004) who demonstrated that Ala substitution at these residues reduced overall phosphorylation of ORF63p.…”
Section: Ms Analyses Identified Multiple Phosphorylated Ser Andsupporting
confidence: 80%
See 1 more Smart Citation
“…Our identification of phosphorylation at Ser224 supports results that demonstrated that Ser224 was a target for CDK1 and that a Ser224Ala mutation altered localization of ORF63p and its transcriptional regulatory properties . Recently, we demonstrated that Ser186 was phosphorylated by CKII (Mueller et al, 2009), which is consistent with this study. Also, our identification of possible phosphorylation at Thr171 and/ or Ser173 (and to a lesser extent Ser12) confirms the work of Baiker et al (2004) who demonstrated that Ala substitution at these residues reduced overall phosphorylation of ORF63p.…”
Section: Ms Analyses Identified Multiple Phosphorylated Ser Andsupporting
confidence: 80%
“…The protein is extensively phosphorylated both in vitro and in vivo by viral and cellular kinases (Baiker et al, 2004;Bontems et al, 2002;Debrus et al, 1995;Habran et al, 2005;Heineman & Cohen, 1995;Kenyon et al, 2001;Mueller et al, 2009;Stevenson et al, 1996;Walters et al, 2008). Computerassisted analysis (http://www.cbs.dtu.dk/services/NetPhos) of ORF63p identified 29 putative Ser, Thr and Tyr phosphorylation sites, including consensus target sequences for casein kinase I (CKI), CKII and cyclin-dependent kinase 1 (CDK1).…”
mentioning
confidence: 99%
“…VZV ORFs 4 and 62 encode regulatory proteins involved in activation of early and late gene transcription (20,24). VZV ORF 63 encodes a highly phosphorylated protein (32) and regulates VZV gene transcription (25), most likely through epigenetic modification of the virus genome (1,15,19). VZV ORF 18 encodes the small subunit of ribonucleotide reductase, an enzyme critical to synthesis of DNA precursors, and also protects neurons from apoptotic cell death (34).…”
Section: Discussionmentioning
confidence: 99%
“…VZV IE63 is a 278 aa protein present in the virus tegument (Kinchington et al, 1995;Sadzot-Delvaux et al, 1998). During productive infection, the highly phosphorylated protein (Mueller et al, 2010) is predominantly located in the nucleus (Mueller et al, 2009). In tissue culture cells, VZV IE63 represses transcription (Di Valentin et al, 2005), most likely through histone modification (Ambagala et al, 2009), as well as reducing translation in response to IFN induction (Ambagala & Cohen, 2007); however, in human ganglia the presence of VZV IE63 is yet to be confirmed, but may function to inhibit VZV-induced apoptosis (Hood et al, 2006;Pugazhenthi et al, 2011).…”
Section: During Latency Hsv-1 and Vzv Gene Transcription Is Restrictedmentioning
confidence: 99%